Postoperative pain and analgesia in patients submitted to unruptured brain aneurysm clamping - Menezes,Míriam Geisa Virgens (2017)
ABSTRACT BACKGROUND AND OBJECTIVES: Adequate postoperative pain evaluation and management are priorities for quality assistance, especially after neurological surgeries. This study aimed at evaluating postoperative pain of neurosurgical patients submitted to unruptured brain aneurysm clamping. METHODS: Prospective and descriptive study carried out in a charity hospital of the city of Aracaju, Sergipe, Brazil. Sample was made up of 28 patients submitted to elective craniotomy for unruptured brain aneurysm clamping. Mann-Whitney, Kruskal-Wallis and Dunn-Bonferroni tests were used for inferential analysis. Significance level was 5% throughout the study. RESULTS: Most patients (78.6%) were females, 64.0% had postoperative pain. There has been significant difference in the number of days with postoperative pain among patients with associated comorbidities (p=0.04) and previous surgery (p=0.01). Most patients had moderate and throbbing headache. There were no adequate pain records and most frequent analgesics were simple analgesics. Opioids prescription was incipient. CONCLUSION: Systematic pain evaluation should be part of multiprofessional assistance, in compliance with international and national pain institutions recommendations.